UPAYA PEMERINTAH INDONESIA DAN WWF-INDONESIA DALAM MENANGGULANGI PENYELUNDUPAN TRENGGILING KE NEGARA TIONGKOK TAHUN 2013-2017 - Sa'diyah, Chalimatus; Pattipelohy, Shary Charlotte (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2019)
The issue of pangolin smuggling to China is still being concern of Indonesian government and various international and non-governmental organizations. One of the international non-governmental organization (INGO) that has a focus on the issue of animal smuggling is World Wide Fund Nature (WWF) - which is an independent foundation that has been registered in accordance with Indonesian law. WWF collaborates with various countries that uphold animal rights, one of which is Indonesia itself. The Indonesian government and World Wide Fund Nature will try to eradicate pangolin smuggling into China. This was done considering the increasing demand for anteater animals from Indonesia to China. This study would like to explain the efforts of the Indonesian government and WWF regarding pangolin smuggling using the approach of internastional cooperation and international organizations. This research argues that the efforts of Indonesia and WWF in responding to pangolin smuggling to China reflect the commitment of international organizations and international cooperation in which Indonesia is one of the country that upholds the value of cooperation between countries.